Taking a picture using a piece of glass - B. Lochana (Nanyang Technological University, 2021)
Taking photos has changed our vision of the world by giving us more access to images drawn from more places and times in the world than we could imagine. It has definitely played a huge part in our lives. Photograph taking involves the use of image sensors called the CMOS (Complementary Metal Oxide Semiconductor) sensor or CCD (charge-coupled device) sensor, which basically converts light into electrical signals. They are usually used to create images in digital cameras, digital video cameras and digital CCTV cameras. The magnitude of the electrical charge at a particular location in the sensor corresponds to the intensity of light falling on it. In this project, I will be taking on a different approach whereby the interaction between light and a dielectric material such as a thin layer of glass results in the light information being encoded as a resistance change. In this project, I will be analysing how this is theoretically and practically possible. The device structure is an oxide material in between two metal electrodes, called the metal–insulator–metal (MIM) structure. I will attempt to find the best condition that makes an image sensor the most effective. This will be done using a transparent oxide. A very good example of a transparent oxide is glass, which essentially is silicon dioxide or SiO2. SiO2 has a large bandgap of above 6 eV, and thus it is non light-absorbing or transparent. The choice is of course not limited to SiO2, any large bandgap transparent oxide could work. In this project, I will be making use of ITO (Tin doped Indium oxide), also a common transparent conducting oxide with a bandgap of about 4 eV.